1979
DOI: 10.1192/bjp.134.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Self-Poisoning — A Complication of Epilepsy

Abstract: From 1972 to 1976 130 epileptics presented 171 times to the Western Infirmary, Glasgow, as medical emergencies with self-poisoning. They constituted 3.5 per cent of 3,733 patients poisoning themselves on 4,121 occasions. Repetition of self-poisoning was commoner in epileptics (18.5 per cent) than in non-epileptics (7.0 per cent). The 130 epileptics have been compared with a non-epileptic group of self-poisoners matched for age, sex, and number of repetitions and have been found to have less alcohol excess but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…Several studies report markedly higher rates of suicide or suicide attempts in epileptic patients [63,64,65,66]. According to one study, 61% of epileptic patients had no follow-up after a suicide attempt by drug overdose [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies report markedly higher rates of suicide or suicide attempts in epileptic patients [63,64,65,66]. According to one study, 61% of epileptic patients had no follow-up after a suicide attempt by drug overdose [64].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report markedly higher rates of suicide or suicide attempts in epileptic patients [63,64,65,66]. According to one study, 61% of epileptic patients had no follow-up after a suicide attempt by drug overdose [64]. In our sample, only a minority of patients (8.7%) had seen a psychiatrist before admission at our center, corroborating once more the notion of a lack of diagnosis of a concomitant psychiatric disorder in patients with chronic epilepsy [67].…”
Section: Discussionmentioning
confidence: 99%
“…Phenobarbital (PB) can cause depression (2,54,(72)(73)(74)(75). It can be associated with the occurrence of suicidal ideation (72) and of suicidal and parasuicidal behavior (52,76,77). Primidone (PRM) (75), tiagabine (TGB), topiramate (TPM) (78), vigabatrin (VGB) (79,80), and felbamate (81) are other AEDs known to frequently cause symptoms of depression.…”
Section: Iatrogenic Factorsmentioning
confidence: 99%
“…Previous studies have found that risk for suicide attempts in epileptics was 4 to 5 times greater as compared to the general population (Trimble & Reynolds, 1987). In this regard, existing findings ascertained that 5% to 7% of epileptics attempted suicide using self-poisoning (Mackay, 1979 ;Hawton et al, 1980 ;Hollaway, 2005).…”
Section: Introductionmentioning
confidence: 97%